1966
DOI: 10.1084/jem.123.1.191
|View full text |Cite
|
Sign up to set email alerts
|

Thymus-Dependent Areas in the Lymphoid Organs of Neonatally Thymectomized Mice

Abstract: Specific areas of lymphocyte depletion, termed thymus-dependent areas, have been delineated in neonatally thymectomized C3H/Bi and F1 (C57BL x C3H/Bi) mice. They occur within the lymphoid follicles of the spleen immediately surrounding the central arterioles, and constitute the mid and deep cortical zones of the lymph nodes. These depleted areas appear in healthy thymectomized mice as early as 3 wk after operation but, in mice which survive for more than 6 to 7 wk, the thymus-dependent areas are repopulated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
105
0
7

Year Published

1967
1967
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 450 publications
(120 citation statements)
references
References 23 publications
8
105
0
7
Order By: Relevance
“…The spleens of these mice were much larger than those of thymectomized irradiated mice. It is possible that the larger spleens trap more thymus cells since these cells preferentially home there rather than to lymph nodes (24,25). Thoracic duct cells, however, have a capacity to recirculate and to home to all the lymphoid tissues (26).…”
Section: Discussionmentioning
confidence: 99%
“…The spleens of these mice were much larger than those of thymectomized irradiated mice. It is possible that the larger spleens trap more thymus cells since these cells preferentially home there rather than to lymph nodes (24,25). Thoracic duct cells, however, have a capacity to recirculate and to home to all the lymphoid tissues (26).…”
Section: Discussionmentioning
confidence: 99%
“…I found dramatic and incontrovertible evidence of high levels of thymus cell migration into blood and immediately into specific zones of lymph nodes, Peyer patches, and spleen-more dramatic when newborn rats were labeled than when adult rats were labeled, but with the same patterns (25). [While on a visit to Mill Hill, I showed my data to Delphine Parrott, who was noting the absence of those zones in thymectomized mice, and she called them thymus-dependent zones of lymphoid secondary organs (26,27).] I showed that the migrants contained cells that could become activated lymphocytes, using Gowans' method of showing the transition of small lymphocytes to large pyroninophilic cells upon alloimmunization.…”
Section: The Thymus Thymic Maturation B Lymphocyte Development Hommentioning
confidence: 99%
“…I showed that the migrants contained cells that could become activated lymphocytes, using Gowans' method of showing the transition of small lymphocytes to large pyroninophilic cells upon alloimmunization. These studies provided the conclusion that the thymus is primarily responsible for the seeding of immunocompetent naive T cells that selectively homed via specialized lymph node and Peyer patch high-walled endothelial postcapillary venules (HEVs) [first described by Gowans as the sites of lymphocyte recirculation from blood to lymphoid organs and back via lymphatics and the thoracic duct to blood (10) into peri-HEV T cells zones, excluding the B cell follicles we later described (26,(28)(29)(30)]. The immigrating thymic migrants could meet antigen and begin the response to antigens that had filtered into LNs, PPs, or spleens (31).…”
Section: The Thymus Thymic Maturation B Lymphocyte Development Hommentioning
confidence: 99%
“…A striking example is an initial report that lymph nodes of thymectomized mice ''showed no proper structures and no plasma cells, often being reduced to a small piece of adipose tissue'' (Miller, 1962). Reports followed stating instead that the deep cortex of the lymph nodes of thymectomized mice is devoid of lymphocytes, hence, it was called a ''thymusdependent zone'' (Parrott et al, 1966) but also a ''T cell area'' or a ''paracortex'' (Goldschneider and McGregor, 1973), however, these terms still conveyed partly unrealistic concepts. The term ''thymus-dependent zone'' is a misnomer (Fossum, 1990) because the deep cortex does form in athymic animals, except that its center is devoid of T cells while its periphery is still populated by B cells (Sainte-Marie et al, 1984).…”
Section: Origin Of Popular Conceptsmentioning
confidence: 99%